Surface MDA8 ozone variability during cold front events over the contiguous United States during 2003–2017. (15th September 2019) - Lei, Ruixue; Talbot, Robert; Wang, Yuxuan; Wang, Sing-Chun; Estes, Mark
Abstract: Cold fronts are mesoscale meteorological phenomena that play important roles in chemical transport processes. Effects of a single cold front episode on surface ozone may vary since meteorological factors may alter ozone in different (increasing or decreasing) directions. We studied cold front events and their effects on surface maximum daily 8-h average (MDA8) ozone over the Contiguous United States (CONUS) during 2003–2017. The average number of cold front days in the CONUS was 50.02 days per year per site with a slightly increasing trend (1.06 per year) during 2003–2017. The Rocky Mountains blocked most cold fronts for the Northwest and the Southwest. Percentages of 24 h back trajectories from north side in 12 sample cities show that cold front effects exist ±12 h to cold fronts' arrival at least. Compared to all days' average, MDA8 ozone differs from prefrontal days, cold front 1st days, cold front 2 + days, and post frontal days by 0.10, −0.94, −0.84, and −1.89 ppbv (−0.89 ppbv on average), respectively. By contrast, they overlapped 9.85%, 5.82%, 0.89%, and 5.04%, respectively (21.60% in total) with ozone exceedance days. Regional consistent long-term effects of cold fronts on surface MDA8 ozone have been found. Enhancements during prefrontal days can be seen in the Northeast and the Midwest during non-winter seasons. For cold front days and post frontal days, ozone differences in the Southwest, the Northwest, and the Northeast were negative in non-winter seasons then reversed to positive in winter. The areas along the coast of the Gulf of Mexico showed positive ozone difference in non-winter seasons and expanded to the inland area during summer then reversed to negative in winter. Synergy of cold fronts and other climatic and meteorological factors (e.g., prefrontal stagnation, southerly flow from the Gulf of Mexico, and winter stratospheric intrusions) can preliminarily explain these consistent long-term effects. Highlights: Cold front effects could exist ±12 h to cold fronts' arrival. Cold fronts showed seasonal consistent effects on surface ozone in some regions. The consistent effects reserved during winter in some regions. Finding common features of cold fronts preliminarily explained consistent effects.